Genesis of giant Early Proterozoic magnesite and related talc deposits in the Mafeng area, Liaoning Province, NE China. (July 2018) - Misch, David; Pluch, Hannes; Mali, Heinrich; Ebner, Fritz; Huang, Hui
Highlights: Magnesite stromatolites and geochemical data indicate primary evaporitic magnesite precipitation in the Early Proterozoic. Initial talc formation in the Mafeng area was single-stage metasomatic. Later iso-chemical remobilization and enrichment formed the present structurally controlled talc deposit. δ 13 C and δ 18 O of magnesites are sensitive to talc formation and hydrothermal processes. The primary (metasomatic) talc mineralization type is partly preserved in the study area. Abstract: This study aims to understand the origin of giant magnesite and talc deposits in the Liaohe Group (Liaoning Province, NE China). Magnesite stromatolites and the composition of fluid inclusions suggest that magnesite or high-Mg calcite precipitated directly from strongly restricted seawater pools with meteoric influx. A primary evaporitic origin is also indicated for parts of the investigated dolomites by comparably heavy δ 18 O values. Later, intense metasomatic activity led to the formation of a magnesite/dolomite succession with irregular contacts and a lighter isotopic signature of oxygen. A slight shift in δ 18 O to more positive values was observed for talc-hosting magnesite, which can be explained by the incorporation of isotopically light oxygen into talc. This highlights that the hydrothermal processes that led to talc formation influenced the hosting carbonates as well, which is also documented by a tendency to smaller crystal sizes, a higher whiteness and lower trace element concentrations in samples from locations nearby large talc bodies. Although δ 13 C is suggested to be less sensitive to hydrothermal activity, comparably light δ 13 C values were determined for magnesite sinters, as well as for remobilized magnesites. In general, the δ 13 C signature of the investigated magnesites is lighter than expected for Proterozoic carbonates. A single-stage generation of the giant talc deposit in the study area is suggested based on elemental and isotopic data. Later deformation led to a (iso-chemical) re-location of talc at least once. During this process, irregularly distributed, cloudy/massive talc bodies acted as weak zones and were incorporated into shear bands up to several meters in thickness, which form the actually present, structurally controlled deposit. The original ore type is preserved only in areas with minor deformation. Lamprophyre dykes prove Jurassic volcanism and are clearly younger than the main phase of talc generation. A younger (post-Jurassic?), intense tectonic event is indicated by strongly tectonized dyke material that is re-worked into strike-slip faults and shows siliceous contact zones to the surrounding magnesite. These faults occasionally cross-cut the older, deposit-forming talc shear bands, indicating that the event that led to the deformation of lamprophyre dykes was younger than the main phase of talc re-location. However, this younger event did not lead to a second phase of major talc generation or affect the quality of the initial deposit to a large extent.